Searching For Personal Identity Of Rango In Gore Verbinski's Movie: Rango (2011): An Individual Psychological Approach - SAFITRI, RAYA GILANG (2012)
The major problem of this study is to elucidate searching for personal identity of Rango reflected in Gore Verbinski's Rango. The objectives of the study are; to analyse the structural elements of the movie and to analyse the character of Rango based on individual psychological perspective. In conducting this study, the researcher uses qualitative research in which the data are based on primary data source, the movie Gore Verbinski's Rango itself. The secondary data are other data which deal with the research. In analysing the data, she applies two analysis, firtsly, structural approach which is uses to analyze the elements of the movie. Secondly, the writer analyze the narrative elements of the movie. The narrative elements consist of characters and characterization, setting plot, point of view and theme. Thirdly, the writer discussed the technical elements of the movie. It overs mise-en-scene, cinematography, sound and editing. Then, the individual psychological approach is used for analysing searching for personal identity of Rango. The writer finds that Rango has important role throughout the story. As human being they tend to have dream in his life. It motivates him to make the dream come true eventhough he uses many ways to catch it.